IMPLEMENTATION OF E-SAPAWARGA SYSTEM IN EFFORTS TO IMPROVE GOVERNMENT SERVICES IN SURABAYA (MAP Observer: Jurnal Penelitian Administrasi Publik, 2021)
The purpose of this study is to describe the use of E-sapawarga in an effort to improve government services in Surabaya. The E-Sapawarga program is run through an application called "Sapawarga". This application is a means to connect the Surabaya City Government with the community which is the target group in implementing the program. Complaints, criticisms and suggestions are facilities offered by the Sapawarga application. The public can freely submit complaints on problems or complaints submitted to the Surabaya City Government through the E-Sapawarga Community. With this application, the public is able to control and supervise the performance of the Surabaya City Government.This study uses the theory of policy implementation. With qualitative descriptive research method. H The results show that the implementation of e-government in the city of Surabaya through the E-Sapawarga program has shown good results. E-government in Surabaya is supported by the availability of adequate information technology and knowledge. However, several obstacles have been found in the Sapawarga application, therefore continuous improvement and development of the Sapawarga application and socialization to the public about the application must continue to be carried out to get the best performance from e-greetings.